(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY To develop a screening tool to optimise neonatal drug prescription, which is often based on low-quality evidence. METHODS Neonatal pharmacotherapy recommendations were identified by literature review and synthesised into NeoCheck tool statements. In a two-round modified Delphi process, experts from Swiss neonatal intensive care units (NICUs) rated their agreement with individual statements using a five-point Likert scale (5 = totally agree). Statements with >65% scores ≥4 in round 1 and >75% scores ≥4 in round 2 were selected. RESULTS We identified 1375 clinical guidelines via literature review. After synthesis, 158 statements were submitted to 23 experts (1 clinical pharmacist, 22 neonatologists; 65% with >10 years neonatology practice) from 10 Swiss NICUs. Nineteen items did not reach the agreement threshold and were eliminated in the second Delphi round. The final NeoCheck tool comprises 141 statements in 11 medical domains concerning 49 neonatal diseases. Most (79%) statements concern all neonates, 13% concern preterm (<37 weeks gestational age) infants and 3% concern very preterm (<32 weeks gestational age) infants CONCLUSIONS NeoCheck is the first prescription-screening tool developed to optimise neonatal pharmacotherapy. In a future prospective study, its effect on NICU prescription optimisation and the quality of care will be assessed.